Pengembangan Usaha Masyarakat Berbasis Industri Kreatif di Desa Saguling Kecamatan Baregbeg Kabupaten Ciamis - Aldi Ahmad Fauzi; R. Rindu Garvera; Ii Sujai (Universitas 17 Agustus 1945 Semarang, Indonesia, 2024)
Economic development carried out at the Village level is the duty and obligation of the Village Government starting with identifying potential, grouping resources, empowering groups or individuals so that they are able to independently develop their potential. The aim to be achieved is to describe the development of creative industry-based community businesses in Saguling Village, Baregbeg District, Ciamis Regency. The research method used by the author is descriptive qualitative research, so that data collection was carried out by carrying out literature studies and field studies (with interviews and observations) and analysis was carried out using data triangulation. This research was carried out in Saguling Village, Baregbeg District, Ciamis Regency. Based on the results of interviews and the author's observations, creative industry-based community business development in Saguling Village, Baregbeg District, Ciamis Regency has not been implemented optimally. This is due to the discovery of problems, including the limitations of business actors in competing with the same competitors, making them unable to survive, then also not wanting to switch to digitizing business products, making business development difficult, and also limited levels of productivity due to limited business capital. business actors are unable to develop.